Evaluation of anti-fungal activity of fractional extracts of Hugonia platysepala on the germs responsible for candidiases in HIV-infected people. Issue 1 (2020) - Couibaly, Ousmane; Mamadou, Mamadou; Dosso, Dosso; Soro, Yaya; Ira, Bonouman; Yapo-Crezoit, Chiaye
No abstract available